92.8k views
25 votes

\boxed{\sf Trigonometry}

Solve for x


\\ \rm\rightarrowtail tan^(-1)x+2cot^(-1)x=(2\pi)/(3)


Note:-

Pls don't answer if you don't know .


Spams and irrelevant answers will be deleted on the spot​

1 Answer

6 votes

Answer:

→x=√3

Explanation:


tan^(-1) x+2cot^(-1) x=(2\pi )/(3) \\\\tan^(-1) x+2((\pi )/(2)-tan^(-1) x)= (2\pi )/(3) \\\\-tan^(-1) x=(2\pi )/(3)-\pi \\\\-tan^(-1) x=-(\pi )/(3) \\\\tan^(-1) x=(\pi )/(3) \\\\x=tan(\pi )/(3) \\\\x=√(3)

User Erik Escobedo
by
5.8k points